2021
DOI: 10.3390/life11030239
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Is Auditory–Verbal Therapy (AVT) for Building Language Development of Children with Cochlear Implants? A Systematic Review

Abstract: This systematic review sheds light on the effectiveness of auditory–verbal therapy (AVT) outcomes in children with cochlear implants (CIs). The presented outcome is based on research findings from the last 10 years. The systematic review was designed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and Critical Appraisal of Treatment Evidence (CATE) checklist. Specific keywords were chosen based on the research question and searched on the PubMed database. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
2
15
0
2
Order By: Relevance
“…Our results support findings from previous studies ( Guerzoni et al., 2016 ; Nicastri et al., 2014 ) providing a more comprehensive evaluation of pragmatics. Globally considered, the existing research suggest that along with early prosthesis, and early verbal and speech rehabilitation ( Binos et al., 2021 ), specialists could also enrich interventions to include programs specifically focused on pragmatic abilities. Indeed, a previous research has shown that the Auditory-Verbal Therapy does not provide a direct effect in improving pragmatic development ( Toe et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results support findings from previous studies ( Guerzoni et al., 2016 ; Nicastri et al., 2014 ) providing a more comprehensive evaluation of pragmatics. Globally considered, the existing research suggest that along with early prosthesis, and early verbal and speech rehabilitation ( Binos et al., 2021 ), specialists could also enrich interventions to include programs specifically focused on pragmatic abilities. Indeed, a previous research has shown that the Auditory-Verbal Therapy does not provide a direct effect in improving pragmatic development ( Toe et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the problems involved in the research on the application of auditory oral method are still focused on the one-way teaching and guidance of professionals for hearing-impaired children and families. AVT can be seen as a tool for CI children to catch up with their NH peers, but future studies need to clarify many weaknesses in the process of evidence and validity 12 .…”
Section: Discussionmentioning
confidence: 99%
“…which was scored 0 ("no"), 1 ("partially") or 2 ("yes"). The total maximum score was 28, with the study quality rated as excellent (26)(27)(28), good (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19) or poor (≤14) [35].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Studies on the efficacy of an AVT parent-centered approach are increasing, and a recent systematic review [ 27 ] concluded that retrospective and longitudinal studies revealed statistically significant improvements in both expressive language and auditory comprehension for children involved in AVT programs compared with other traditional approaches, such as total communication, bilingual-bicultural or auditory-oral methods. Limitations in the quality of the published studies, however, make the results difficult to generalize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation